2021
DOI: 10.1038/s41420-021-00431-1
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation enhances the cholinergic anti-inflammatory pathway to reduce lung injury in acute respiratory distress syndrome via STAT3

Abstract: The cholinergic anti-inflammatory pathway (CAIP) is important for antagonizing inflammation and treating several diseases, including acute respiratory distress syndrome (ARDS), and is related to vagus nerve integrity. However, its underlying pathophysiological mechanism is still unclear. We hypothesized that CAIP regulates lung injury repair after ARDS through the STAT3 signaling pathway, which is an important downstream effector of α7nAchR. We enhanced CAIP activity by subjecting rats to vagus nerve stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…2d ). 107 Thus, it is important to know if there is any specificity of the close interactions between MMs and the types of enteric axons they surround.…”
Section: Muscularis Macrophages Interact With the Ensmentioning
confidence: 99%
“…2d ). 107 Thus, it is important to know if there is any specificity of the close interactions between MMs and the types of enteric axons they surround.…”
Section: Muscularis Macrophages Interact With the Ensmentioning
confidence: 99%
“…LPS stimulation induced phosphorylation of p65 which significantly decreased in the presence of GTS-21. Dependent on the cell type, the JAK2/signal transducer and activator of transcription 3 (Stat3) as well as the PI3K/protein kinase B (Akt) signaling pathway have been reported to mediate the cholinergic anti-inflammatory mechanism ( 42 48 ). To identify involved signaling components leading to LPS-induced IL-8 suppression after a7nAChR stimulation we used selective inhibitors specific for Jak2/3 (tyrphostin AG490) and PI3K (wortmannin).…”
Section: Resultsmentioning
confidence: 99%
“…However, the effects of STAT3 on lung tissue were not dogmatic. Previous study found that vagus nerve stimulation played a protective role in acute respiratory distress syndrome by increasing STAT3 and regulating macrophage transformation ( Li et al, 2021 ). The diverse functions of STAT3 may be related to the different mechanisms of STAT3 in different cells types.…”
Section: Discussionmentioning
confidence: 99%